37th Structure, Structural Dynamics and Materials Conference 1996
DOI: 10.2514/6.1996-1383
|View full text |Cite
|
Sign up to set email alerts
|

Response surface approximations for discipline coordination in multidisciplinary design optimization

Abstract: The practical application of optimization methods to non-hierarchic, coupled, multidisciplinary systems has been hampered by the costs associated with the use of complex discipline-speci c analysis procedures. When the cost of performing these individual analyses is high, it is impractical to apply many current optimization methods to most practical systems in order to identify improved designs. This paper details an extended formulation and application of the Concurrent Subspace Optimization (CSSO) approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…of unknown coeffi- » (P),(P) (7) Note that there is a difference between the p th vector of independent variables, x( p ), and the p th vector of independent variables mapped into the form of the polynomial model, x( p ).…”
Section: Polynomial Approximation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…of unknown coeffi- » (P),(P) (7) Note that there is a difference between the p th vector of independent variables, x( p ), and the p th vector of independent variables mapped into the form of the polynomial model, x( p ).…”
Section: Polynomial Approximation Modelsmentioning
confidence: 99%
“…In addition, the method of least squares used in creating the models is relatively computationally inexpensive and straightforward. Evidence of the popularity of polynomial modeling is given by the wealth of recent reports both by the authors of this document [2] and by others as well (cf., [3,4,5,6,7,8,9]). …”
Section: Introductionmentioning
confidence: 98%
“…The objective is to determine the least gross take-off weight design within the bounded design space, subject to two performance constraints. The MDO formulation of the aircraft concept sizing problem is posed as Minimize: W total W empty • W f uel (16) •W paylaod Subject to: g 1 Range Range required 1 0 0 0 It is observed that the RS-CSSO method takes far fewer iterations to converge to the same optimum as obtained by LANCELOT. The solution reached by both algorithms is recognized as the global optimum of the problem.…”
Section: Aircraft Concept Sizing Problemmentioning
confidence: 99%
“…Additionally, approximation models and sensitivity analysis are implemented and applied to predict missing data in the database. [5][6][7] Analysis methods are developed for aerodynamics, propulsion and performance. [8][9][10] These analysis codes are implemented in a spreadsheet using the well-known Visual Basic for applications (VBA) programming language for simple and efficient calculation.…”
Section: Process and Methodologymentioning
confidence: 99%